FACTORS THAT INFLUENCE THE SELECTION OF AR RAHNU AMONG MUSLIM CONSUMERS AT SUNGAI PETANI, KEDAH - Che Khadijah Hamid; Hamizah Muhammad; Che Zuina Ismail; Nur Syahirah Md Zain; Rubiah Abu Bakar (Journal of Islamic, Social, Economics and Development, 2022)
Any item that can be pawned that can help get money from the pawning of the item is counted as ar-rahnu. this study was conducted to find out and identify the factors that influence muslim users in Sungai Petani, kedah towards ar-rahnu contracts or pawning in islam. The research objective to analyse the demographics of Muslim consumers in choosing Ar Rahnu and to indentify the factors that influence the choosing of Ar-Rahnu among Muslim consumers at Sungai Petani, Kedah. Quantitative method was applied in this study through distribution of a total of 150 questionnaire as a research instrument to Muslim users in Sungai Petani, Kedah. A snowball sampling technique was used whereby an online structured questionnaire was developed using Google forms, with a consent form appended to it. The link of the questionnaire was sent through WhatsApp application and spread among several groups especially local community groups who was advised to circulate it in the community. Descriptive analysis was used to analyse the data in the form of percentage, frequency, mean, mode and median. The results of the study found that the mean value shown in each variable was at a high level, i.e part B was 3.9725 and part C was 4.2627 which was also at a high level. At the end of the study, the researcher suggested that further and more in-depth research about Ar-Rahnu be made to Islamic users so that they can know more about it. The results of this study are expected to be a reference for other researchers in the future and can help them make studies specifically about Ar-Rahnu.